iLearning: Metode Pembelajaran Inovatif di Era Education 4.0 - Rahardja, Untung; Lutfiani, Ninda; Harahap, Eka Purnama; Wijayanti, Lidya (Technomedia Journal, 2020)
Education 4.0 (education 4.0) is a general term used by educational theorists to understand various ways to integrate cyber technology both physically and not into learning. The role of information technology in higher education has been understood in academic activities. Information and communication technology in academics is very helpful and helpful in the educational process where the teaching and learning process, arranging schedules in the room, and other tasks are easy and very practical. The use of 4.0 education in every internal and external activity in higher education is one of the factors of the success and progress of higher education, one of which is in the Raharja College with iLearning learning methods such as; MeMe and iDu. By using mind mapping and literature study methods. This study aims to foster creative and innovative for lecturers, teachers, students, and students and also can create a person full of work and the success of the nation.